EValuation of Acute and Early Phase P2Y12 Inhibitor DE-escalation After Percutaneous Intervention (EVADE PCI) - Presnell, Erica N; Andrea M Bond; Jessica Hernandez (Kansas Journal of Medicine, 2025)
Introduction. Aspirin and an oral P2Y12 inhibitor are recommended for one year after percutaneous coronary intervention (PCI) in patients with acute coronary syndromes. While ticagrelor or prasugrel are preferred over clopidogrel, de-escalation often is based on provider judgment. This study compared cardiovascular outcomes and bleeding risks between patients who remained on ticagrelor or prasugrel (unchanged group) and those de-escalated to clopidogrel within 30 days of PCI. Methods. We analyzed data from patients admitted between June 2014 and December 2022 for acute coronary syndromes requiring PCI who received an oral P2Y12 inhibitor within 72 hours of admission. The primary outcome was a composite of all-cause mortality, urgent revascularization, stent thrombosis, stroke, and major bleeding at one year. Secondary outcomes included individual components of the composite outcome. Statistical analyses included chi-square tests, Student’s t-tests, or non-parametric equivalents. Results. A total of 210 patients met the inclusion criteria, with 149 remaining on unchanged P2Y12 therapy and 61 undergoing de-escalation. There was no statistically significant difference in the composite outcome between the unchanged and de-escalated groups (n [%]: 25 [17] vs. 6 [10]; χ² [1, N = 210] = 1.658, p = 0.198). Additionally, secondary outcomes did not differ significantly between groups. Conclusions. A composite outcome of all-cause mortality, urgent revascularization, stent thrombosis, stroke, and major bleeding at one year was similar between patients who continued ticagrelor or prasugrel and those de-escalated to clopidogrel within 30 days of PCI. Larger studies are needed to confirm these findings and assess optimal timing for therapy adjustments.